Long‐term efficacy and safety of sucroferric oxyhydroxide in African American dialysis patients. Issue 4 (15th April 2018) - Sprague, Stuart M.; Ketteler, Markus; Covic, Adrian C.; Floege, Jürgen; Rakov, Viatcheslav; Walpen, Sebastian; Rastogi, Anjay
Abstract: Introduction: Sucroferric oxyhydroxide (SFOH) is a non‐calcium, iron‐based phosphate binder that demonstrated sustained serum phosphorus (sP) control, good tolerability, and lower pill burden, vs. sevelamer carbonate ("sevelamer"), in a Phase 3 study conducted in dialysis patients with hyperphosphatemia. This analysis evaluates the efficacy and safety of SFOH and sevelamer among African American (AA) patients participating in the trial. Methods: Post hoc analysis of a 24‐week, Phase 3, open‐label trial (NCT01324128) and its 28‐week extension study (NCT01464190). Patients were randomized 2:1 to SFOH (1.0–3.0 g/day) or sevelamer (2.4−14.4 g/day) for up to 52 weeks. Findings: Of 549 patients who completed the Phase 3 study and extension, 100 (18.2%) AA patients were eligible for efficacy analysis (SFOH, n = 48; sevelamer, n = 52). sP concentrations decreased rapidly and comparably with both treatments by Week 8 (mean ± standard deviation change from baseline: −1.9 ± 1.9 mg/dL for SFOH and −2.2 ± 1.8 mg/dL for sevelamer). These reductions were maintained for 52 weeks (−2.1 ± 2.6 and −2.1 ± 1.6 mg/dL) and achieved with a lower mean pill burden (3.4 ± 1.4 vs. 7.6 ± 2.9 tablets/day) with SFOH vs. sevelamer. Treatment adherence rates (adherence within 70%–120% of expected medication intake) were 79.2% with SFOH and 59.6% with sevelamer. The proportion of patients reporting serious adverse events (AEs) was 27.7% with SFOH and 30.7% with sevelamer. More patients withdrew due to treatment‐emergent AEs with SFOH vs. sevelamer (18.5% vs. 8.0%). The most common AEs with both treatments were gastrointestinal‐related: diarrhea and discolored feces with SFOH, and nausea, vomiting, and constipation with sevelamer. Discussion: SFOH is an efficacious and well‐tolerated treatment for hyperphosphatemia in AA dialysis patients, with a lower pill burden and an improved adherence rate vs. sevelamer. These findings were consistent with the wider US patient population and the overall study population.